2020
DOI: 10.1002/jnr.24690
|View full text |Cite
|
Sign up to set email alerts
|

Impact of network‐targeted multichannel transcranial direct current stimulation on intrinsic and network‐to‐network functional connectivity

Abstract: Dynamics within and between functional resting‐state networks have a crucial role in determining both healthy and pathological brain functioning in humans. The possibility to noninvasively interact and selectively modulate the activity of networks would open to relevant applications in neuroscience. Here we tested a novel approach for multichannel, network‐targeted transcranial direct current stimulation (net‐tDCS), optimized to increase excitability of the sensorimotor network (SMN) while inducing cathodal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 70 publications
1
24
0
Order By: Relevance
“…due to less or more responding based on task difficulty), we opted to focus on right parietal coverage. While verbal working memory storage and rehearsal are more associated with left-lateralized regions of parietal cortex (Awh et al, 1996;Ravizza et al, 2004), some meta-analytic data demonstrate bilateral parietal activation across verbal and non-verbal N-back tasks (Mencarelli et al, 2019;Owen et al, 2005) Gross ROIs from the montage (used in subsequent figures) were defined based on the Brain AnalyzIR Toolbox's depth map function (Santosa et al, 2018). Depth maps show the distance from each fNIRS optode to the superficial cortex of several talairach daemon labeled regions of the Colin27 atlas (Lancaster et al, 2000), which can be used to determine coverage of an ROI based on the montage used.…”
Section: Fnirs Optode Locations (Montage)mentioning
confidence: 99%
See 1 more Smart Citation
“…due to less or more responding based on task difficulty), we opted to focus on right parietal coverage. While verbal working memory storage and rehearsal are more associated with left-lateralized regions of parietal cortex (Awh et al, 1996;Ravizza et al, 2004), some meta-analytic data demonstrate bilateral parietal activation across verbal and non-verbal N-back tasks (Mencarelli et al, 2019;Owen et al, 2005) Gross ROIs from the montage (used in subsequent figures) were defined based on the Brain AnalyzIR Toolbox's depth map function (Santosa et al, 2018). Depth maps show the distance from each fNIRS optode to the superficial cortex of several talairach daemon labeled regions of the Colin27 atlas (Lancaster et al, 2000), which can be used to determine coverage of an ROI based on the montage used.…”
Section: Fnirs Optode Locations (Montage)mentioning
confidence: 99%
“…One of the more well-studied effects in fMRI and fNIRS is that of cognitive loaddependent changes in frontal and parietal cortical regions (Cui et al, 2011;Fishburn et al, 2014;Herff et al, 2014;Mencarelli et al, 2019;Owen et al, 2005). That is, neural activity in these regions increases with more cognitively taxing and difficult tasks.…”
Section: Introductionmentioning
confidence: 99%
“…There are two different paradigms: intermittent TBS (iTBS) and continuous TBS (cTBS). While iTBS facilitates CE, cTBS attenuates it (45)(46)(47)(48)(49). The advantage of TBS as compared to low and high frequency rTMS is that by using a similar number of pulses but considerably shorter duration and lower intensity of stimulation, experimental time is reduced without jeopardizing effect strength.…”
Section: Transcranial Magnetic Stimulationmentioning
confidence: 99%
“…Computational modeling studies suggested that current flow is mostly focused under the stimulated electrode ( 53 ), although human imaging studies showed that tDCS could even modulate spinal network excitability ( 60 ), which is in line with animal studies showing spread of tDCS-related effects to subcortical networks ( 61 ). Novel approaches emerged to improve spatial targeting, such as high definition transcranial current stimulation (HD-tCS) ( 62 ) or network-targeted multichannel stimulation (net-tCS) ( 63 , 64 ) that make use of multiple electrodes improving focality.…”
Section: Non-invasive Brain Stimulation: Basic Priniciples and Findings In Chronic Musculoskeletal Painmentioning
confidence: 99%
“…tACS can be targeted to different cortical brain regions depending on the electrode montage. A recent method for optimizing the configuration of multifocal tACS for stimulation of specific brain networks ( 28 , 29 ) has been developed. Such multifocal brain network targeting achieves a more significant behavioral and physiological impact than traditional tACS approaches using two large electrodes ( 30 ).…”
Section: Introductionmentioning
confidence: 99%